2002
DOI: 10.1115/1.1510526
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effective Large Blade Components by Using Carbon Fibers

Abstract: For large off-shore wind turbines, blades with relative low blade mass are becoming more important. The economic use of large-tow carbon fibers can help achieve lower blade masses. Basic material design data have been established for two promising material combinations, including the fatigue properties for Panex33/epoxy. Blade root joints have been developed in a carbon/glass combination, resulting in a better price performance ratio. The initial cost assessment on a blade dominated by severe fatigue loads sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…In a European research effort, carbon fiber composites were investigated for potential improvements in blade weight and cost [1][2][3][4]. Under the Global Energy Concepts, LLC (GEC)/Sandia Blade System Design Study, carbon fiber material was identified as cost effective for use in the load bearing spar structure [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In a European research effort, carbon fiber composites were investigated for potential improvements in blade weight and cost [1][2][3][4]. Under the Global Energy Concepts, LLC (GEC)/Sandia Blade System Design Study, carbon fiber material was identified as cost effective for use in the load bearing spar structure [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the strain data for compression was calculated by MSU based on the measured (constant) value of the tensile modulus. In both tension and compression, the single-cycle strain values (Table 5- 6) showed only modest variation between the epoxy and VE resins. The single-cycle tensile strain was higher than the static value measured at Intec (Table 5- 5), and the compressive single-cycle strains were lower than the corresponding static measurements.…”
Section: Infused Fiberglass Fatigue Resultsmentioning
confidence: 98%
“…These growth trends have been accompanied by extensive research and development efforts in the blade manufacturing industry. In addition, government-funded programs in both Europe [2][3][4][5][6] and the United States [7][8][9] have been investigating alternative blade design and material technologies. Technical challenges include restraining weight growth, enabling larger rotors by increased stiffness, improving power performance, mitigating loads, facilitating transportation, and designing for fatigue cycles on the order of 10 7 .…”
Section: Introductionmentioning
confidence: 99%
“…An important method to increase the operational wind turbine efficiency is to increase the blade length [ 11 , 12 , 13 , 14 , 15 ]. This is even more important for off-shore turbines, which tend to be larger than on-shore turbines [ 16 , 17 , 18 ]. Most wind turbine blades consist of a spar flange and shear webs that are covered by an aerofoil (see Figure 2 ), all of which are typically made of glass fibre composites [ 10 ].…”
Section: Introductionmentioning
confidence: 99%